PENGARUH STRATEGI KOMUNIKASI, KUALITAS WEBSITE DAN KONTEN MEDIA INSTAGRAM TERHADAP CITRA PEMERINTAH KOTA DENPASAR PADA BAGIAN PROTOKOL DAN KOMUNIKASI PIMPINAN SEKRETARIAT DAERAH KOTA DENPASAR - I Wayan Agus Yuliawan; I Nyoman Yoga Segara; I Gede Sutarya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The use of social media, particularly Instagram by local government can quickly reach everyone. Through social media, the government can provide direct and open contributions, get feedback, allow commenting and share information quickly and without limits. This research aims to determine the effectiveness of using Instagram to improve the image of the Denpasar City Government through interactions and feedback from social media followers as a form of public information openness, implemented by the Public Relations Department in responding to news and promoting a positive image in the community. This research found that Communication Strategy, Website Quality and Instagram Content have an impact on the Government's Image. Although each independent variable can influence the dependent variable, significant results will only occur if all variables are implemented optimally.